A comprehensive comparison of the methylomes between three Russian wheat aphid biotypes differing in virulence and associated bacteria - De Jager, Nicholas Stratos (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.